Prosthetic Rehabilitation of Partial Ear Defect: 2 Case Reports - Subaşı, Meryem Gülce (J Indian Prosthodont Soc, 2013)
The loss or absence of an auricle may result from trauma, disease or congenital anomalies and causes a considerable aesthetic problem. If the deformity involves the external auditory canal, it can affect hearing. This case report describes the surgical and prosthetic treatment of two patients with partial defects of their right external ears from different causes. Implant-retained auricular prostheses fabricated from heat-temperature-vulcanised silicone were used in both the cases; they were designed to be harmonious with the remaining tissues. The patients experienced improved retention, aesthetics, hearing and quality of life with these prostheses. During the approximately 3 year follow-up, both the prostheses were re-fabricated once; however, problems related to implant stability and peri-implant tissue health were not encountered.